2020
DOI: 10.3390/molecules25225263
|View full text |Cite
|
Sign up to set email alerts
|

The Qualitative and Quantitative Compositions of Phenolic Compounds in Fruits of Lithuanian Heirloom Apple Cultivars

Abstract: As the interest in heirloom cultivars of apple trees, their fruit, and processed products is growing worldwide, studies of the qualitative and quantitative composition of biological compounds are important for the evaluation of the quality and nutritional properties of the apples. Studies on the variations in the chemical composition of phenolic compounds characterized by a versatile biological effect are important when researching the genetic heritage of the heirloom cultivars in order to increase the cultiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Apple flesh and peel samples were prepared as described by Butkeviciute et al [ 33 ]. Extracts of apple flesh and peel samples were prepared as described by Butkeviciute et al [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Apple flesh and peel samples were prepared as described by Butkeviciute et al [ 33 ]. Extracts of apple flesh and peel samples were prepared as described by Butkeviciute et al [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Samples of whole apples and apple peels were prepared as described by Butkeviciute et al [86]. Extracts of whole apple samples were prepared as described by Butkeviciute et al [87]. Extracts of apple peel samples were produced: 2.5 g of the lyophilized powder (exact weight) was weighed, added to 25 mL of 2% hydrochloric acid solution in 70% (v/v) ethanol, and was extracted in an ultrasonic bath Sonorex Digital 10 P (Bandelin Electronic GmbH & Co. KG, Berlin, Germany) at room temperature for 20 min.…”
Section: Preparation Of Apple and Apple Peel Extractsmentioning
confidence: 99%
“…Reynoutrin (Figure 1) is a natural flavonoid that exists in the leaves and fruits of a variety of natural plants and has been shown to have potential antioxidant and antiviral properties (Ho et al, 2012;Rehman et al, 2018;Butkevičiūtė et al, 2020;Santos et al, 2021). In the preliminary experiments, we found that reynoutrin can effectively improve cardiac function in rats with IHF caused by permanent left anterior descending coronary artery (LAD) ligation, as well as significantly up-regulate the protein expression of S100 calciumbinding protein A1 (S100A1) in myocardial tissue.…”
Section: Introductionmentioning
confidence: 97%